The genomic characterization of carbapenemase-producing Serratia marcescens at a tertiary hospital in South Africa - Overmeyer, Amanda (Department of Pathology, 2024)
Background Serratia marcescens is an opportunistic nosocomial pathogen, and recent reports have highlighted the rapid increase in multidrug resistance in this organism. There is a paucity in genomic data for carbapenem resistant S. marcescens (CRSM). Methods A retrospective cohort study describing laboratory confirmed CRSM from a tertiary academic hospital in Cape Town, South Africa, for the period 2015-2020, was performed. Stored CRSM and control isolates were submitted for whole-genome sequencing using Illumina MiSeq, with the Nextera DNA Flex Library Preparation Kit. Sequence data was analysed in-house using srst2 and Tychus, and CRSM and control isolates were compared. Results Twenty-one CRSM and four control isolates were sequenced and analysed. Twenty-four different resistance genes were identified, with all isolates having at least two resistance genes, and seventeen isolates harbouring three or more genes. This correlated well with phenotypic results. The blaOXA-48-like carbapenemase was the most common carbapenemase identified in 86% (18/21) of CRSM. A core SNP difference tree indicated that the CRSM could be grouped into three clusters. A minority of isolates had shared plasmids. Several genes and single nucleotide polymorphisms (SNPs) were identified in the CRSM which may putatively augment virulence, but this requires further functional characterisation. Conclusion A diverse resistome was observed in CRSM, which was also reflected phenotypically, with blaOXA-48-like the most common carbapenemase. Though distinct clusters were observed, no clonality was noted, and a limited number of isolates shared plasmids. This study provides genomic data for emerging CRSM and highlights the importance of ongoing genomic surveillance to inform infection prevention control and antimicrobial stewardship initiatives.